Historical data of atmospheric electric field observations in Japan. Issue 1 (29th January 2022) - Nagamachi, Shingo; Arita, Shin; Hirota, Eiji
Abstract: The Kakioka Magnetic Observatory (KMO) of the Japan Meteorological Agency (JMA) made atmospheric electric field observations at Kakioka and Memambetsu beginning in 1929 and 1949, respectively, and ending in February 2021 and December 2010, respectively. The digital numerical data are available on the KMO website, although not all observation periods are covered. In this article, we introduce the available datasets and summarize the metadata regarding the observations, such as measurement instruments, maintenance methods and data processing. Abstract : The Kakioka Magnetic Observatory (KMO) of the Japan Meteorological Agency (JMA) made atmospheric electric field observations at Kakioka and Memambetsu from 1929 to 2021 and from 1950 to 2010, respectively. These long‐term stationary observations are highly unique and have contributed to investigations of the atmosphere.